2018
DOI: 10.18203/2349-2902.isj20184644
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of fistula in ano in patients attending surgical OPDs of a tertiary care teaching hospital, Central India

Abstract: Background: A fistula-in-ano is an abnormal hollow tract or cavity that is lined with granulation tissue and that connects a primary opening inside the anal canal to a secondary opening in the perianal skin; secondary tracts may be multiple and can extend from the same primary opening.Methods: All cases of clinically diagnosed fistulae-in-ano admitted in various surgical units in Index Medical College Hospital, Indore during the study period January 1, 2015 to December 31, 2017. A Preformed set of questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…16 Also in current study, perineum discharge was the commonest symptom in all cases (100%) and which was either continuous or intermittent in nature as similar to the previous studies. 1,[17][18][19][20][21] Almost all cases had one opening either on one side of midline to right or left and anterior or posterior to the anal opening. Only two cases had 2 openings each in this present series.…”
Section: Resultsmentioning
confidence: 99%
“…16 Also in current study, perineum discharge was the commonest symptom in all cases (100%) and which was either continuous or intermittent in nature as similar to the previous studies. 1,[17][18][19][20][21] Almost all cases had one opening either on one side of midline to right or left and anterior or posterior to the anal opening. Only two cases had 2 openings each in this present series.…”
Section: Resultsmentioning
confidence: 99%
“…15 Qureshi et al reported 80% posterior fistula and 20% anterior fistula. 13 Yadu S et al reported 76% posteriorly located fistula. 14 In a study by Kumar HM et al, 66% were posterior fistulae, 24% anterior, and 10% lateral fistulae.…”
Section: Discussionmentioning
confidence: 98%
“…12 Qureshi et al reported discharge in 75% of patients. 13 Yadu S et al reported discharge in 74% of patients. 14 Our study reports are like those previously reported, the absence of discharge could suggest a quiescent nature of the fistula which is possibly a part of the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation